Fermi acceleration on the annular billiard - De Carvalho, R. Egydio [UNESP]; Souza, F. Caetano [UNESP]; Leonel, Edson D. [UNESP] (American Physical Society (APS), 2006)
We study the phenomenon of unlimited energy growth for a classical particle moving in the annular billiard. The model is considered under two different geometrical situations: static and breathing boundaries. We show that when the dynamics is chaotic for the static case, the introduction of a time-dependent perturbation allows that the particle experiences the phenomenon of Fermi acceleration even when the oscillations are periodic. © 2006 The American Physical Society.